Management Strategies of Village-Owned Enterprises in Tanjungharjo Village, Bojonegoro - Syafaat, M. Nur Ali; Eprilianto, Deby Febriyan (SERUNAI, 2023)
One of the efforts that the Indonesian government can undertake to boost the local economy is by encouraging Village-Owned Enterprises, known as “Badan Usaha Milik Desa” or BUM Desa, to become more active. In the case of Tanjungharjo Village, there is a BUM Desa named Tanjungkarya. However, during its implementation, various obstacles were encountered, such as a lack of financial resources, human resources, infrastructure, and effective programme management. This research aimed to describe the Management Strategies of the Village-Owned Enterprise (BUM Desa) for developing the community's economy in Tanjungharjo Village, Kapas Sub-District, Bojonegoro Regency. The study employed a qualitative approach with a descriptive method, and informant selection is based on purposive sampling. The informants consist of the Village Head of Tanjungharjo, the Secretary of Tanjungharjo Village, the Chairman of BUM Desa Tanjung Karya, the Secretary of BUM Desa Tanjung Karya, the Treasurer of BUM Desa Tanjung Karya, and members of the Tanjungharjo community. Data was collected through observation, interviews, and documentary analysis. The data was then analysed through data reduction, data presentation, and drawing conclusions. The research focused on six criteria based on Koteen's strategy, which are 1) organisational strategy, 2) resource strategy, and 3) programme strategy. The research findings indicate that the management strategies of the Village-Owned Enterprise (BUM Desa) to enhance the local economy in Tanjungharjo Village encompass three main aspects. First, in the organizational strategy aspect, there was a formulation of a vision and mission involving various stakeholders, and the implemented programmes align with the vision and mission set by BUM Desa Tanjung Karya. Second, regarding the resource-supporting strategy, there were still several hindrances that impede the optimisation of this strategy. Third, regarding the programme strategy, this pertained to the evaluation and implementation of programmes. Based on the programmes conducted by BUM Desa Tanjung Karya, they had contributed to the Village Revenue (PAD) for the Tanjungharjo Village Annual Village Budget (APB Desa). Thus, the management strategies of BUM Desa had not been fully executed optimally due to the presence of these obstacles.